Reliability and validity validation of the Chinese version of the family vitiligo impact scale - Jian Sun; Linna Li; Xue Tian; Yuping Fu (BMC Public Health)
Abstract Background The Family Vitiligo Impact Scale (FVIS) is the first reliable and valid instrument to evaluate the psychological and social impact on family members with vitiligo. However, the FVIS has not yet been validated in China. Objective This study aimed to adapt the FVIS across cultures and utilize a cross-sectional design to validate its reliability and validity in evaluating the quality of life of family members with vitiligo in China. Methods The original version scale was first translated into Chinese using Brislin back- translation method. This study was conducted among adult individuals in China (N = 348). The participants were aged 18 to 70 years, with a mean age of 33.6 years (SD = 11.3). The sample consisted of 50.9% females (n = 177) and 49.1% males (n = 171). Respondents completed the Chinese versions of the FVIS and Family Dermatology Life Quality Index (FDLQI). Exploratory factor analysis (EFA) and confrmatory factor analysis (CFA) were used to test the construct validity of the scale, and the content validity of the scale was assessed through the content validity index. The internal consistency of the scale was assessed by calculating Cronbach’s alpha coefcient, Omega coefcient, split-half reliability, and test-retest reliability. Results EFA supported a three-factor structure, explaining 79.208% of cumulative variance. CFA demonstrated satisfactory construct validity for the FVIS, with excellent model fit: chi-square degree of freedom (χ2/df) = 2.019, root mean square error of approximation (RMSEA) = 0.072, standardized root mean square residual (SRMR) = 0.0145, Comparative Fit Index (CFI) = 0.983, and Tucker Lewis Index (TLI) = 0.978. The content validity index of the scale was 0.979. The Cronbach’s alpha coefcient was 0.975, Omega coefcient was 0.964, the split-half reliability coefcient was 0.977, and the test–retest reliability was 0.959. Conclusion The Chinese FVIS showed satisfactory reliability and validity for assessing vitiligo’s psychosocial impact on family membersin Chinese clinical and research settings.